Learning styles vs. virtual education preferences: a cross-sectional study on medical sciences e-students - Karimian, Zahra; Zolfaghari, Zahra (Frontiers in Education, 2024)
E-students sometimes feel isolated due to the lack of face-to-face communication with teachers. It is important to pay attention to students’ learning styles and the virtual education methods used by teachers. This study aimed to investigate the preferences of students at Shiraz University of Medical Sciences (SUMS) regarding virtual education and their learning styles. A descriptive survey research was conducted on postgraduate e-students in 2019-2020. A stratified random sampling was performed among 300 students from four virtual master’s programs at SUMS. A total of 180 questionnaires were distributed, and 155 samples completed the questions. The VEPQ questionnaire was used to measure the participants’ virtual education preferences, while the VARK standard questionnaire was utilized to determine their learning styles. The data were analyzed using SPSS 24 software via one-sample T-tests, independent T-tests, and ANOVA tests. All students exhibited a unimodal learning style, with their dominant style being reading/writing (P < 0.05). All educational methods received scores higher than the cut-off point (P < 0.01). Students’ virtual education preferences were as follows: e-content (5.26 ± 0.74), self-directed projects (4.70 ± 0.90), face-to-face modules (4.67 ± 1.14), online presentations (4.32 ± 0.94), and text interaction (3.98 ± 1.18). There was no significant difference in students’ virtual education preferences based on their learning styles (P > 0.05). E-students have different learning styles, but their educational preferences are more influenced by their circumstances. Therefore, the use of multimedia and independent learning is essential for them. It can be stated that “flexibility,” “personalization,” and “independence” are the three main preferences of e-students that should be considered in educational planning.